Structural and Vibrational Investigation of Benzil-(1,2-Diphenylethane-1,2-Dione): Experimental and Theoretical Studies - N. Kanagathara; K. Senthilkumar; V. Sabari; V. Ragavendran; S. Elangovan (Journal of Chemistry)
Single crystals of benzil commonly known as 1,2-diphenylethane-1,2-dione are grown by the slow evaporation method at room temperature. Gaussian 09 program is applied for theoretical calculations with B3LYP/6-311++G(d,p) basis set. The structure is optimized, and the energy, structural parameters, vibrational frequencies, IR, and Raman intensities are determined. Complete natural bonding orbital (NBO) analysis is carried out to analyze the intramolecular electronic interactions and their stabilization energies. From the second-order perturbation theory analysis of the benzil molecule, it is observed that there exists a hyperconjugative intramolecular stabilization energy between 17.45 and 22.76 KJmol-1. HOMO-LUMO analysis has been performed to identify the charges transferred within the molecule. The energy gap is calculated to be 2.919 eV and thus establishes the soft nature of the molecule. The molecular electrostatic potential (MEP) of the grown crystal was analyzed using the B3LYP method with 6-311++G(d,p) basis set. First-order hyperpolarizability calculations reveal the nonlinear optical microscopic behavior of the benzil molecule with nonzero values. The total value of the first-order hyperpolarizability (βtot) is of the order of 41.5246×10−31 esu, which is found to be 11.135 times that of urea. Hence, benzil can be referred to as a good material for nonlinear optical applications.